Prevalence of Helicobacter pylori cagA and vacA genes in Cypriot patients - George Krashias; Stavros Bashiardes; Alexia Potamitou; George S Potamitis; Christina Christodoulou (Journal of Infection in Developing Countries)
Introduction: The prevalence of H. pylori varies with geographic locations. To date there are no epidemiological data on its prevalence in Cyprus; therefore, we determined the prevalence and molecular characteristics of H. pylori infection in Cypriot patients.